PTH-042 A Feasibility, Pilot Study of Endoscopic Ultrasound Guided Solid Gold Marker Fiducial Placement in Oesophageal Cancer in Radiotherapy Planning. (17th August 2016) - Paterson, S; McIntosh, D; Grose, D; MacLaren, V; Stanley, AJ
Abstract : Introduction: There have been several different methods proposed for image guided radiotherapy in oesophageal cancer patients. One method described recently has been a fiducial solid gold marker sited under direct EUS guidance. 1 Methods: This was a single centre, prospective, feasibility pilot study in a tertiary care cancer centre in Glasgow. Patients with oesophageal cancer, in whom radiotherapy was being planned between October 2015 and February 2016, underwent EUS to place solid gold fiducial markers of length 5 mm. 4 of these fiducials, in a new multi-fiducial delivery system (Cook®) with a 22 g delivery needle, were inserted through the channel of a linear EUS scope. The needle was inserted into the tumour and fiducials placed into the tumour under EUS guidance. 2 markers were placed at both the distal and proximal margin of the tumour where possible. The Five-point Likert scale 2 was used to determine technical outcomes from EUS placement at both EUS and planning CT. Median Likert scores are reported. Time to place the fiducial at time of EUS and any complications were recorded. Results: A total of 25 fiducials have been placed in 7 patients. In 2 patients the tumour limited the passage of the EUS scope distally; therefore only proximal placement of the fiducials was undertaken. The median EUS accuracy of fiducial placement was within 5 mm from the outer rim of the target (Likert 2) and fiducials were deployed with minimal difficulty (Likert 2). The needle was clearly seen and easy to distinguish from surrounding tissue (Likert 1) and the fiducial markers were easy to see with minimal adjustments to the scope (Likert2). Mean time for fiducial deployment at EUS was 345 seconds. Mean time from EUS to planning CT scan was 28 days. At the planning CT fiducials were visualised in the tumour region in 6 of 7 patients. In these 6 patients they were visible in the tumour areas where placement was undertaken. The total number of fiducials identified was 15 out of 25 sited and they were easy to distinguish from surrounding tissue (Likert 2). There have been no complications reported. Conclusion: EUS guided solid gold marker fiducial deployment is safe and feasible in patients with oesophageal cancer. There appears to be good correlation between fiducial position at EUS and subsequent radiotherapy planning CT. This may help to better target radiotherapy delivery. References: 1 Endoscopy/EUS-guided fiducial marker placement in patients with esophageal cancer. GastrointestEndosc . 2015 Oct;82 (4):641–9. doi:10.1016/j.gie.2015.03.1972. 2 Evaluation of a new endoscopic ultrasound-guided multi-fiducial delivery system: Digestive Endoscopy, 25 :615–621. doi:10.1111/den.12046 Disclosure of Interest: None Declared